FLAVONOID COMPOUNDS IDENTIFIED IN ALCHEMILLA L. SPECIES COLLECTED IN THE NORTH-EASTERN BLACK SEA REGION OF TURKEY - Kaya, Bülent; Menemen, Yusuf; Saltan, Fatma Zerrin (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
This study identified flavonoid glycosides in species of the genus Alchemilla, A. procerrima, A. stricta, A. hirtipedicellata and A. sericata. A. procerrima is an endemic species for Turkey. After detailed investigation, flavonoid compounds of the species were identified for the first time. In this study, flavonoid compounds were determined by using two different chromatography techniques, TLC and HPLC. The following flavonoid compounds were identified from the Alchemilla species studied. They are as follows: orientin (luteolin-8-C-glucoside) Rf: 0,70, vitexin (apigenin-8-C-glucoside) Rf: 0,77 as flavone-C-glycoside, rutin (quercetin-3-O-rutinoside) Rf: 0,44, hyperoside (quercetin-3-O-galactoside) Rf: 0,65, isoquercetin (quercetin-3-O-glucopyranoside) Rf: 0,72, quercitrin (quercetin-3-O-rhamnoside) Rf: 0,84 as flavonol-O-glycoside. Three more folavonoids with Rf values of Rf1= 0,36, Rf2=0,54 and Rf3=0,68 were also identified for the first time in this study. Rutin (quercetin-3-O-rutinoside) and the flavonoid glycoside, shown as Rf2 were found in all species. Quercitrin and isoquercetin were determined in all analysed species but A. procerrima. Hyperoside was identified in all species except for A. stricta. Vitexin was determined only in A.stricta. Orientin was determined in A. procerrima and A. stricta, but could not be determined in A. sericata and A. hirtpedicellata. Unknown flavonoid with Rf1 and Rf3 were determined outside of A. sericata. Description of these compounds in Turkish Alchemilla plants for the first time should be viewed as a discovery of an important chemosystematic feature.